The potential due to a source moving through a compressible fluid and applications to some rotary derivatives of an aerofoil - Westley, R. (College of Aeronautics, Cranfield, 1952)
The first part of this note concerns the evaluation of the potential at a fixed point in space due to an arbitrarily moving source. Continues …